Zakres podmiotowy prawa do petycji w Niemczech - Wichrowski, Filip Zygmunt (Wydawnictwo Naukowe UAM, 2018)
The subject of this article is the right to petitions specified in Article 17 of the Basic Law of the Federal Republic of Germany. This provision regulates the individual’s right to address requests and complaints to public authorities. This publication contains an analysis of this institution with regard to entities that are entitled to exercise this right, as well as entities obliged to consider submitted petitions. The author begins the analysis of the indicated institution be reviewing the evolution of the historical right to petition, which has evolved from the institution of supplication known in ancient Rome. He indicates changes in the subjective scope of the right to petitions, focusing on the achievements of German constitu- tionalism in the 19th century. Next, the current regulation that guarantees the right to petition in Germany in its normative environment is presented. The public authorities that are the addressees of the petition have been analysed, and the scope of duties associated with receiving a complaint or request indicated. Furthermore the author describes particular types of entities that are guaranteed the right to submit petitions under the Basic Law of the Federal Republic of Germany. In this respect, various kinds of restrictions of this right, depending on the type of the petitioner, are identified. The last part of the work contains the characteristics of various forms of petitions due to the type of author and the addressee. Various functions which currently are fulfilled by the institution of petitions were subjected to analysis. In this context, a distinction was made between individual petitions and collective petitions, tak- ing into account their subject matter and the aims intended by the petitioner. The author also shows the future possibility of a development of the discussed institution, describing the public petition to the Bundestag, which has an electronic form.
The subjective scope of rights to petition in Germany
Keywords: petition; subjective scope; Germany